2010
DOI: 10.1167/iovs.09-4217
|View full text |Cite
|
Sign up to set email alerts
|

Visual Experience–Independent Functional Expression of NMDA Receptors in the Developing Rabbit Retina

Abstract: These results indicate that NMDA receptors participate in the synaptic maturation of retinal circuits during the early stages of development but that the functional NMDA receptors, including their subunit composition, in the developing rabbit retina are independent of the rabbit's visual experience.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 83 publications
0
12
0
Order By: Relevance
“…AGB labeling secondary to endogenous (basal) or exogenous (ligand) activation reports on the cation entry history of the cell and not the summed excitation/inhibitory history (Marc et al, 2005). Guanidinium compounds like AGB permeate cation channels and are immunodetectable when only a small fraction of glutamate receptors have been activated (Picco and Menini, 1993; Marc et al, 2005) using short incubation times secondary to ligand activation (Marc, 1999a,b; Michel et al, 1999; Edwards and Michel, 2003; Marc et al, 2005; Sun and Kalloniatis, 2006; Acosta et al, 2007; Edwards et al, 2007; Chang and Chiao, 2008; Mobley et al, 2008; Chang et al, 2010; Chen and Chiao, 2012). Factors that will affect AGB labeling include cell volume, channel size, number of open channels, ligand affinity of receptor channel, channel permeation, and channel desensitization (Marc, 1999a,b; Marc et al, 2005; Sun and Kalloniatis, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…AGB labeling secondary to endogenous (basal) or exogenous (ligand) activation reports on the cation entry history of the cell and not the summed excitation/inhibitory history (Marc et al, 2005). Guanidinium compounds like AGB permeate cation channels and are immunodetectable when only a small fraction of glutamate receptors have been activated (Picco and Menini, 1993; Marc et al, 2005) using short incubation times secondary to ligand activation (Marc, 1999a,b; Michel et al, 1999; Edwards and Michel, 2003; Marc et al, 2005; Sun and Kalloniatis, 2006; Acosta et al, 2007; Edwards et al, 2007; Chang and Chiao, 2008; Mobley et al, 2008; Chang et al, 2010; Chen and Chiao, 2012). Factors that will affect AGB labeling include cell volume, channel size, number of open channels, ligand affinity of receptor channel, channel permeation, and channel desensitization (Marc, 1999a,b; Marc et al, 2005; Sun and Kalloniatis, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, Xue et al [42] have shown by immunoblotting an increase in total NR1 protein levels at P12 and P60 rat retinas using 1 week dark rearing, while dark rearing from birth did not cause detectable changes in total NR1 immunoreactivity in rabbit and rat retinas [27,41]. This discrepancy between changes in mRNA and protein levels of expression might be attributed mainly to the different sensitivities of the methodologies, or to the different species used.…”
Section: Discussionmentioning
confidence: 99%
“…The distribution of NMDAR subunits in the mammalian retina has been studied at the mRNA and protein level, as well as during development [19][20][21][22][23][24][25][26][27]. In rat retina, the NR1 subunit mRNA is expressed in virtually all neurons in the retinal ganglion cell (RGC) and inner nuclear layer [19].…”
Section: Introductionmentioning
confidence: 99%
“…This implies that it has important functions in the emergence of specific retinal circuits (Chang et al, 2010). In addition, in the developing rat retina, the NMDARs can play essential roles in mediating neural plasticity.…”
Section: +mentioning
confidence: 99%
“…Chang et al (2010) reported that the expression of NR1 and NR2A/B receptor subunits of NMDAR was independent of visual experience and that light deprivation did not influenced the functional NMDARs in the developing retina of the rabbit.…”
Section: +mentioning
confidence: 99%